Prediction of cross polarization discrimination at millimeter wave band due to dust storms - Abdulwaheed, Musa; Bashir, Saad Osman (Asian Research Publishing Network (ARPN), 2013)
Microwave links performance during dust storms has received considerable interest in recent time with emphasis on signal attenuation. However, phase shift and cross polarization have not been tackled enough. This paper investigates the cross polarization discrimination (XPD) induced by dust storms at millimetre wave band. It introduces simple models of wave propagation through dust storms. The models are developed based on the forward scattering amplitude of dust particles using Rayleigh method. Three conditions are set to validate the suitability of the Rayleigh approximation for the model. It is shown that the method is valid for determining the scattering of ellipsoidal dust particles for the particle sizes and frequency range considered. The scattering coefficients are derived and mathematical models for phase shift and attenuation are proposed in terms of relative permittivity and visibility. Results of the proposed model compared with some published results show close agreement. Differential phase shift and attenuation are computed and XPD introduced by dust storms in such links are predicted using the model parameters as inputs. Attenuation in dry dust is only significant when the visibility becomes severe. XPD at such visibility also becomes significant i.e. numerically low. A similar trend is found as the frequency increases.